2007
DOI: 10.1161/strokeaha.106.473462
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Dynamic Cerebral Autoregulatory Response to Cyclic Stimuli

Abstract: Background and Purpose-Dynamic cerebral autoregulation has been shown to be fast and effective, but it is not well known if the mechanism is symmetric, that is to say, it acts with equal compensatory action to upward as compared with downward abrupt changes in arterial blood pressure (ABP). Methods-Fourteen patients with head injuries and 10 normal subjects had bilateral transcranial Doppler and continuous ABP recording. Cyclic ABP stimuli were generated by large thigh cuffs, which were rapidly inflated above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 21 publications
(27 reference statements)
4
100
1
Order By: Relevance
“…In 2007 Aaslid et al [7] reported the combined use of three Hokanson 1 units (i.e., a controller, an air source unit and a timer) to drive bilateral thigh cuffs on and off at a constant frequency of 0.05 Hz. Their system did not allow changes in frequency or other controls, and also did not incorporate the ability to assess reactivity to CO 2 changes.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007 Aaslid et al [7] reported the combined use of three Hokanson 1 units (i.e., a controller, an air source unit and a timer) to drive bilateral thigh cuffs on and off at a constant frequency of 0.05 Hz. Their system did not allow changes in frequency or other controls, and also did not incorporate the ability to assess reactivity to CO 2 changes.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the classical single inflation/release of thigh cuffs 3 or the fixed frequency square wave inflation/deflation approach, 20 PRBS-controlled inflation/deflation of thigh cuffs present several important advantages. First of all, the method allows the time during which the cuffs remain inflated to be much reduced compared with the conventional thigh cuff test, 16 thus reducing patient discomfort and minimizing the possibility of increased sympathetic activity, as indicated by the stable HR values in Table 2.…”
Section: Assessment Of Dynamic Cerebral Autoregulation E Katsogridakimentioning
confidence: 99%
“…Although it is assumed that this reflex vasomotion is equally effective in attenuating both cerebral hypoperfusion and hyperperfusion, 7 dCA may be more adept at compensating for transient hypertension than for hypotension, as induced by cyclic inflation and deflation of thigh cuffs. 8 However, extrapolation of these data to healthy individuals needs to be done with caution, because asymmetry was only apparent in head-trauma patients under conditions of artificial ventilation and hypocapnia. Furthermore, thigh cuffs only elicited minor changes in blood pressure (Ϸ8 mm Hg).…”
mentioning
confidence: 99%